The impact of gross domestic product, exchange rates and ACFTA implementation on Indonesia’s trade intensity index - Wardani, Dyah Titis Kusuma; Huda, Adinda Salshabilla Zhauza; Darsono, Susilo Nur Aji Cokro; Duasa, Jarita (Universitas Muhammadiyah Yogyakarta, 2024)
The ASEAN-China Free Trade Area (ACFTA) represents a critical agreement between ASEAN member countries and China, aimed at fostering economic integration by eliminating or reducing trade barriers, enhancing service market access, refining investment regulations, and bolstering economic cooperation. This framework is designed to strengthen economic ties and enhance welfare across the involved nations. This study evaluates the impact of the ACFTA on trade dynamics by analyzing the Trade Intensity Index (TII), GDP, exchange rates, and a dummy variable representing the ACFTA's implementation. Utilizing annual data from 2001 to 2021, sourced from the UN-Comtrade Database and the World Bank, the research employs the Ordinary Least Squares (OLS) method to provide insights into the trade relationships under the ACFTA framework. The findings indicate a divergent impact, while Indonesia experiences a negative and significant influence from GDP, exchange rates, and ACFTA implementation, the ASEAN-6 countries display a positive and significant effect. Moreover, the study reveals that Indonesia's Trade Intensity Index with other ACFTA members is comparatively lower than Malaysia’s. This suggests a need for targeted trade policies in Indonesia aimed at amplifying export volumes in sectors where it holds a comparative advantage. Such strategies could significantly enhance Indonesia's trade intensity within the ACFTA, fostering greater economic integration and benefits under this expansive regional trade agreement.